La mirada confusa de Barrio (1998). Estereotipos y violencia contra las mujeres en la España de finales de los noventa - Mercedes Álvarez San Román (Cahiers de Civilisation Espagnole Contemporaine)
In this article, I analyze how cinema can contribute to the naturalization of the relationships between women and men. In order to identify how the symbolic violence is exercised, I will focus on the Spanish successful movie from the 90s, Barrio (1998), directed by Fernando León de Aranoa. This feature film was produced and released during a turning point in the perception of gender violence, when the society assumed that it was a public problem and not an individual issue. For that reason, I will study the different ways of imposing power as seen through this movie, from one of the subtlest, such as the diffusion of stereotypes, to the most extreme, like violence against women.